Impact of minimally invasive procedures on hospital stay and disease staging in patients with colorectal cancer - Danylenko, Oleksandr; Piskorskyi, Oleksandr (The Ukrainian Scientific Medical Youth Journal, 2026)
Introduction. Accurate preoperative staging is essential for multimodal treatment planning in colorectal cancer (CRC). Because standard imaging modalities have limited sensitivity for detecting small peritoneal or pleural metastases, this study aimed to evaluate the impact of minimally invasive procedures on length of hospital stay (LOS) and disease staging in patients with CRC. Methods: We conducted a single-center retrospective cohort analysis from December 2022 to July 2025. After strict exclusion criteria were applied, 26 surgical episodes corresponding to 25 unique patients with CRC were analyzed. Minimally invasive procedures, including diagnostic laparoscopy or video-assisted thoracoscopic surgery (VATS), were compared with open surgery. The primary outcome was LOS. Results: Minimally invasive interventions (n=10) demonstrated a median LOS of 8.5 days (IQR, 5.2-13.0) versus 10.5 days (IQR, 7.0-18.0) for open surgery (p=0.289). Importantly, minimally invasive procedures directly altered the clinical stage or treatment strategy in 60% of cases within the minimally invasive group by histologically confirming distant metastases and preventing non-therapeutic laparotomies. Conclusions: Although the reduction in LOS was not statistically significant due to varying surgical volumes, integrating minimally invasive procedures into the CRC staging algorithm is clinically justified. These procedures ensure precise staging and prevent unnecessary open surgical trauma.